Lessons Learned and Perceptions of 21st Century Skills Development among Thai Students in an Intercampus Student Camp - Sae-Jane, Pikun; Chairee, Thanarphong (Sripatum Review of Humanities and Social Sciences, 2026)
This research aimed to measure the 21st-century skills of Thai students through a participatory learning process implemented via a relationship-building camp. A mixed-methods research design was employed. Data were collected from 97 students across six institutions using questionnaires and interviews. Quantitative data were analyzed using statistical software, while qualitative data were examined through content analysis. The findings revealed that, overall, students perceived their development of 21st-century skills at the highest level ( = 4.56). When examined by individual skill dimensions, statistically significant differences were found at the .05 level (F = 6.119, p = 0.000). The dimension of cross-cultural understanding and paradigm awareness received the highest mean score ( = 4.65). This reflects that the relationship-building camp functioned as an integrative learning space conducive to skill development through hands-on practice and reflective thinking. Participants engaged in problem-solving in real-time, developed an appreciation for diverse cultures, overcame prejudices, and fostered positive interpersonal relationships. Moreover, the camp served as a safe environment that stimulated transformative learning, influencing attitudes, personality traits, and self-confidence. The key finding of this research is that extracurricular activities designed upon the foundation of experiential learning can serve as a significant mechanism for holistically fostering 21st-century skills. Such activities should be systematically designed to effectively link learning experiences with tangible skill outcomes.